2022
DOI: 10.1007/s10995-022-03377-7
|View full text |Cite
|
Sign up to set email alerts
|

Building the MCH Public Health Workforce of the Future: A Call to Action from the MCHB Strategic Plan

Abstract: Introduction In 2021, the Maternal and Child Health Bureau (MCHB) released a new strategic plan to guide its work over the next 10–15 years. The plan highlights four goals—access, equity, workforce capacity, and impact—that are essential to achieving MCHB’s vision. Methods We present 13 recommendations to highlight opportunities for ongoing and new activities aligned with Goal 3 of the plan—“Strengthen Public Health Capacity and Workforce for MCH.” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…A good talent plan can help increase the effectiveness of a talent, which is characterized by a high level of competence, ability, and willingness to work, resulting in lower financial costs and a corresponding balance of supply and demand. Understanding project needs-based resources and talent planning are some of the latest management methods for predicting quantitative and qualitative needs, which are supported by Bonifaci [3] and Ramos et al [39].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A good talent plan can help increase the effectiveness of a talent, which is characterized by a high level of competence, ability, and willingness to work, resulting in lower financial costs and a corresponding balance of supply and demand. Understanding project needs-based resources and talent planning are some of the latest management methods for predicting quantitative and qualitative needs, which are supported by Bonifaci [3] and Ramos et al [39].…”
Section: Discussionmentioning
confidence: 98%
“…This paper also found that the strategic planning for human resources has an effect on the performance of project management for infrastructure companies in Jordan due to demographic variables (company age, company capital, and company project size), where companies gain more experience with the number of years they operate, and capital helps assess the value of projects that the company can use. The size of the company also affects its productivity and the size of projects that can be received, as mentioned by Baporikar [13], Ramos et al [39] and Rauzana and Dharma [40].…”
Section: Discussionmentioning
confidence: 99%
“…11 Key advantages of these partnerships to public health departments include buttressed workforce development, greater access to subject matter experts, and increased use of evidence-based practices; collectively, these contribute to enhanced health service capability and patient care quality. [12][13][14] For the academic sector, these partnerships engender opportunities for research, external funding, and student field-based training. [15][16][17] They also afford academics a pathway to mission-driven, applied contributions.…”
Section: Introductionmentioning
confidence: 99%
“…Goal 3 ( Strengthen Public Health Capacity and Workforce for MCH ) supports the future of the MCH public health workforce with 13 recommendations. These recommendations are described in the Ramos et al article ( 2022 ) included in this special issue, and discuss the trajectories for MCH public health careers, high-quality training, and how to build the MCH workforce capacity and skills to address inequities and social determinants of health. Additional recommendations address the need to build a diverse workforce, increase community engagement, and mobilize people with lived experiences in service to MCH populations.…”
mentioning
confidence: 99%